PERLINDUGAN HUKUM TERHADAP KORBAN KEJAHATAN TINDAK PIDANA NARKOTIKA BERKAITAN DENGAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Nugraha, Sandi; Windyastuti, Feny (IBLAM LAW REVIEW, 2022)
Narcotics and psychotropics are drugs or materials that are useful in the fields of treatment, service, health, and scientific development, and on the other hand can cause very detrimental dependence if used without supervision, strict and careful supervision. Article 27 paragraph (1) of the 1945 Constitution affirms "All citizens have the same position in law and government and are obliged to uphold the law and government with no exceptions". The article shows that everyone has the right to recognition, guarantee of protection, and fair legal certainty as well as equal recognition before the law. The research method used is normative legal research with the sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials uses a documentary study technique and the technique of analyzing legal materials used is a qualitative technique. The results of the study indicate that legal protection for victims of narcotics crime has not been implemented in the Perspective of Law Number 35 of 2009 concerning Narcotics, causing injustice and legal uncertainty and future criminal law policies in providing legal protection to victims of narcotics abusers must not only reform criminal law. material, but also reforming formal criminal law and criminal law enforcement.